Design of a voltage collapse monitoring device using local information - Myo Oo, Myint Thein. (2009)
This project developed a MATLAB GUI application to monitor the voltage collapse point of 3-phase 4-wire power system using locally available information which can be read using a microprocessor-based multi-instrument unit called the MIC. The three methods used to monitor in this project are “Thevenin”, “V-I characteristic” and “Voltage Stability Index”. The result will show as line graph on the display window of MATLAB developed program in real-time. This will be useful for predicting voltage stability of the power system so that the power black out or voltage collapsing can be protected.